Perforated Meckel's diverticulum - Gatto, Janaina (2017)
We report a patient with diffuse peritonitis due to perforation of Meckel's diverticulum. This patient was referred to the operating room and underwent bowel resection segment encompassing the area of the diverticulum and terminoterminal primary enteroanastomosis on two levels with good evolution. The diverticulum complications are often related to the presence of ectopic mucosa, especially the gastric and pancreatic type. Since preoperative diagnosis is difficult and infrequent, in most cases this anomaly is confirmed only during surgery. Surgical resection of the affected intestinal segment is the mainstay of treatment in both diverticula diagnosed incidentally, as the complicated by inflammation, bleeding, obstruction or perforation. We conclude that in cases of acute abdomen punctured, the diagnosis of Meckel's diverticulum should be considered.